2008
DOI: 10.1158/0008-5472.can-07-2103
|View full text |Cite
|
Sign up to set email alerts
|

CCN3/Nephroblastoma Overexpressed Matricellular Protein Regulates Integrin Expression, Adhesion, and Dissemination in Melanoma

Abstract: CCN3/nephroblastoma overexpressed belongs to the CCN family of genes that encode secreted proteins associated with the extracellular matrix (ECM) and exert regulatory effects at the cellular level. Overexpression of CCN3 was shown in metastatic melanoma cells compared with cells of the primary tumor from the same patient. Analysis of short-term cultures from 50 primary and metastatic melanomas revealed a heterogeneous expression pattern of both the 46-kDa fulllength cytoplasmic/secreted protein and the 32-kDa … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 41 publications
5
52
0
Order By: Relevance
“…Whereas some studies suggest that CCN3 exerts growth suppressive effects on glioma, melanoma, and breast cancer cells, [13][14][15] others support a prometastatic role for this protein in melanoma. 16 CCN3 can impair the proliferation of Ewing's sarcoma cells but promote their migration and invasion, 17 supporting the observed association between high CCN3 levels and metastatic disease in this cancer type. 18,19 Finally, high CCN3 levels correlate with poor outcome in patients with osteosarcoma or prostate cancer.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Whereas some studies suggest that CCN3 exerts growth suppressive effects on glioma, melanoma, and breast cancer cells, [13][14][15] others support a prometastatic role for this protein in melanoma. 16 CCN3 can impair the proliferation of Ewing's sarcoma cells but promote their migration and invasion, 17 supporting the observed association between high CCN3 levels and metastatic disease in this cancer type. 18,19 Finally, high CCN3 levels correlate with poor outcome in patients with osteosarcoma or prostate cancer.…”
mentioning
confidence: 69%
“…58,59 These observations are in agreement with a recent study demonstrating that CCN3 increases the metastatic potential of melanoma cells without affecting subcutaneous growth rates. 16 CCN3 can impair the proliferation of Ewing's sarcoma cells and diminish their tumorigenicity in vivo while enhancing the migratory and invasive phenotype of Ewing's sarcoma cells. 17 Moreover, high CCN3 levels are associated with increases in the incidence of metastatic disease in patients with Ewing's sarcoma.…”
Section: Ccn3 and Breast Cancer Bone Metastasis 2385mentioning
confidence: 99%
“…The role of CCN3 in the establishment of visceral metastases was supported by the observation that SCID mice injected with cells stably expressing CCN3 developed a much higher number of hepatic metastatic metastases than the mice injected with CCN3 negative tumor cells (Vallacchi et al 2008). …”
Section: Dr Jekyllmentioning
confidence: 98%
“…Nevertheless, these data are partially in contrast with studies that showed CCN3 anti-proliferative activity in vitro (Benini et al, 2005;Fukunaga-Kalabis et al, 2008a). Moreover, it has been seen that, while CCN3 expression is decreased in cutaneous melanoma metastasis (Fukunaga-Kalabis et al, 2008a), its expression is copious in visceral metastases (Vallacchi et al, 2008), probably due to the capacity of this protein to specifically address melanoma tumor cells to metastasize visceral organs, such as SPARC acts towards lung metastases.…”
Section: Ccn3 (Nephroblastoma Over-expressed Gene)mentioning
confidence: 76%
“…Concerning CCN3, whose expression is in reverse correlation to neoplastic progression of a melanoma, many experiments on both induction and silencing have been performed using cell and animal models, with subsequent alterations in the cell capacity to adhere to laminin and vitronectin (Vallacchi et al, 2008).…”
Section: Ecm Proteins As Molecular Targets In Melanoma Therapymentioning
confidence: 99%